2016
DOI: 10.1038/srep18551
|View full text |Cite
|
Sign up to set email alerts
|

Mapping female bodily features of attractiveness

Abstract: “Beauty is bought by judgment of the eye” (Shakespeare, Love’s Labour’s Lost), but the bodily features governing this critical biological choice are still debated. Eye movement studies have demonstrated that males sample coarse body regions expanding from the face, the breasts and the midriff, while making female attractiveness judgements with natural vision. However, the visual system ubiquitously extracts diagnostic extra-foveal information in natural conditions, thus the visual information actually used by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 42 publications
(62 reference statements)
0
7
1
Order By: Relevance
“…This corresponds to the previously mentioned unrealistic slim-thick body image [ 13 ]. This WHR of around 0.65 from influencers on Instagram is less than the previously idealized 0.7 that is mentioned in the literature [ 21 , 24 , 25 , 26 ]. The study participants’ preferred a WHR that broadly matched those of the fitness influencers, but not when Japan is viewed in isolation, where a participant-preferred WHR of 0.738 was found compared with the influencer’s WHR of 0.685.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…This corresponds to the previously mentioned unrealistic slim-thick body image [ 13 ]. This WHR of around 0.65 from influencers on Instagram is less than the previously idealized 0.7 that is mentioned in the literature [ 21 , 24 , 25 , 26 ]. The study participants’ preferred a WHR that broadly matched those of the fitness influencers, but not when Japan is viewed in isolation, where a participant-preferred WHR of 0.738 was found compared with the influencer’s WHR of 0.685.…”
Section: Discussioncontrasting
confidence: 56%
“…Therefore, an assumption can be made that the WHR is a universal transcultural dogma. Actually, a preference for a WHR of 0.7 was shown in many cultures [ 21 , 24 , 25 , 26 ]. A study of pre-industrial people in Tanzania showed a preference for heavier women and the WHR played a minor role.…”
Section: Introductionmentioning
confidence: 99%
“…One can argue that dieting in an obesogenic environment is an adaptive strategy for women approaching reproductive age to maximize their attractiveness. 63 , 64 The increasing rates of “muscularity-oriented eating disorders” in men are consistent with this hypothesis, as strength and fitness are important sexual selection pressures for males. 65 , 66 However, although dieting is very common, additional vulnerability factors are necessary for the development of eating disorders.…”
Section: Epidemiological Link Between the Obesity Epidemic And Eatingmentioning
confidence: 60%
“…We consider first a subset of participants from Bovet, Lao, Bartholomée, Caldara, & Raymond, (2016), as a demonstration bootstrap-clustering approach (Algorithm 2) thresholds on cluster extent. Notice that the FWERs of panels a and b are computed at the pixel level (i.e., the proportions of false-positive pixels across simulations), and the FWERs of panels c and d are calculated at the test level (i.e., the percentages of any false positives per test for the 1,000 simulations).…”
Section: Examplementioning
confidence: 99%